2010
DOI: 10.1002/jts.20497
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder symptoms and functional impairment among OEF and OIF National Guard and Reserve veterans

Abstract: The aims of the present investigation were (a) to examine associations between posttraumatic stress disorder (PTSD; diagnosis and symptoms) and different aspects of functioning, severity, and subjective distress among Operation Iraqi Freedom and Operation Enduring Freedom National Guard and Reserve veterans, and (b) to examine the unique contribution of PTSD symptom clusters to different aspects of functioning and distress. Participants were 124 veterans who had returned from war-zone deployment. A PTSD diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
102
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 32 publications
7
102
6
Order By: Relevance
“…Thus, it may be important for treatment to target these additional symptom domains in order to achieve functional recovery. These findings contrast with previous work identifying avoidance/numbing (Rona et al, 2009; Shea et al, 2010) and hyperarousal symptoms (Heir et al, 2010; Maguen et al, 2009) as being significantly related to functional impairment among individuals with PTSD. To our knowledge, this is the first study to investigate DSM-5 PTSD symptom dimensions in relation to functional impairment, which may account for these discrepant findings, given the differences in PTSD symptom domains between DSM-5 and DSM-IV-TR.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, it may be important for treatment to target these additional symptom domains in order to achieve functional recovery. These findings contrast with previous work identifying avoidance/numbing (Rona et al, 2009; Shea et al, 2010) and hyperarousal symptoms (Heir et al, 2010; Maguen et al, 2009) as being significantly related to functional impairment among individuals with PTSD. To our knowledge, this is the first study to investigate DSM-5 PTSD symptom dimensions in relation to functional impairment, which may account for these discrepant findings, given the differences in PTSD symptom domains between DSM-5 and DSM-IV-TR.…”
Section: Discussioncontrasting
confidence: 99%
“…The study of functional impairment may be particularly relevant among veteran samples, where individuals with PTSD experience poorer health functioning, increased disability (Goldberg et al, 2014), greater functional impairment, and reduced quality of life compared to veterans without PTSD (Shea, Vujanovic, Mansfield, Sevin, & Liu, 2010; Zatzick et al, 1997). Moreover, among trauma-exposed men, combat trauma has been related to greater incidence of PTSD, unresolved PTSD symptoms, and unemployment (Prigerson, Maciejewski, & Rosenheck, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies have shown associations between PTSD and objective indicators of quality of life (QOL) such as homelessness and unemployment [12][13]. Such impairments are common among populations at high risk for PTSD, such as military personnel deployed to combat [3,[5][6][8][9][10][11][12][13][14]. Research suggests that these impairments are currently affecting many Veterans of the wars in Iraq and Afghanistan (Operations Iraqi Freedom and Enduring Freedom) and are therefore important to identify and treat [15].…”
Section: Introductionmentioning
confidence: 99%
“…The last decades have seen a plethora of research on the toll of recent wars in Iraq and Afghanistan (Andersen, Karstoft, Bertelsen, & Madsen, 2014; Carlson et al, 2010; McDevitt-Murphy et al, 2010; Ramchand et al, 2010; Schnurr et al, 2010; Shea, Vujanovic, Mansfield, Sevin, & Liu, 2010). Many studies have aimed at estimating the prevalence of PTSD following deployment and have reported greatly varying rates.…”
Section: Introductionmentioning
confidence: 99%